Civil Rights and Arbitration - Irving Kovarsky (Washington University Law Quarterly, 1974)
One area of arbitration in need of close scrutiny today is the civil rights arena. For the purposes of this Article, the meaning of “civil rights” is limited to situations involving employer or union discrimination on the basis of race, religion, nationality, sex, or age. While employers and unions generally respect and abide by arbitration awards in civil rights disputes, do employee grievants find—and should they find—equal comfort? Although I believe the need for reform is much more extensive, this Article is primarily devoted to civil rights issues brought to arbitration. Specifically, it addresses the question of whether arbitration is a just means of adjudicating civil rights disputes. State and federal legislation require “fair employment” by employers and unions; yet, arbitrators resolving civil rights disputes function under controls which retard, or at least hinder, advancement toward “fair employment.” To support the argument for reform, I will review the legal regulation of arbitration and examine the arbitration process itself. I will also present empirical evidence which points to the shortcomings of arbitration in civil rights disputes and suggest reforms.
Keywords: Race discrimination; Industrial arbitration; Civil rights